На шляху до якісного оновлення роботи українських судів - Марфіна, Н.В. (Інститут держави і права ім. В.М.Корецького НАН України, 2009)
Статья посвящена комплексному и всестороннему изучению существующих проблем в организации деятельности судов Украины. На основе проведенного анализа предложены пути устранения существующих недостатков. Учитывая опыт Днепровского районного суда г. Киева, в работе изложены новые формы и методы организации рабочего процесса, которые апробированы судом и успешно используются в его деятельности. Приведены преимущества работы модельной формы организации труда в суде, при этом особое внимание уделено Украинско-канадскому проекту судебного сотрудничества. The article is devoted the complex and comprehensive study of existent problems in organization of activity of courts of Ukraine. On the basis of the conducted analysis the ways of removal of the existent failings are offered. Taking into account experience of the Dneprovskiy district court of city of Kiev, new forms and methods are in-process expounded organizations of working process, which are tested a court and successfully used in his activity. Advantages are resulted robots of model form of organization of labors in a court, here the special attention is spared the Ukrainian-сanadian project of judicial collaboration.